2013
DOI: 10.1016/j.febslet.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid – Driven gene regulation

Abstract: Phospholipids (PLs), well known for their fundamental role in cellular structure, play critical signaling roles via their derivatives and cleavage products acting as second messengers in signaling cascades. Recent work has shown that intact PLs act as signaling molecules in their own right by modulating the activity of nuclear hormone transcription factors responsible for tuning genes involved in metabolism, lipid flux, steroid synthesis and inflammation. As such, PLs have been classified as novel hormones. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 128 publications
3
39
0
Order By: Relevance
“…These conformational variations are also in line with the prior HDX data showing conformational variation between the same structural elements (i.e. the alternate AF, the AF2, and in H8 and H9) (1).…”
Section: Ligand and Co-regulator Drive Differential Effects On Localsupporting
confidence: 90%
See 1 more Smart Citation
“…These conformational variations are also in line with the prior HDX data showing conformational variation between the same structural elements (i.e. the alternate AF, the AF2, and in H8 and H9) (1).…”
Section: Ligand and Co-regulator Drive Differential Effects On Localsupporting
confidence: 90%
“…Recent evidence, however, suggests intact PLs are able to directly modulate the activity of transcription factors involved in lipid homeostasis, such as sterol regulatory element-binding protein 1 (SREBP-1), and some members of the nuclear receptor (NR) family of ligand-regulated transcription factors, including peroxisome proliferator-activated receptor ␣ (PPAR␣; NR1C1), steroidogenic factor 1 (NR5A1), and human liver receptor homolog-1 (LRH-1; NR5A2) (1)(2)(3)(4). LRH-1 regulates the expression of genes central to embryonic development, cell cycle progression, steroid synthesis, lipid and glucose homeostasis, and local immune function (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The human liver receptor homologue-1 (LRH-1; 3 NR5A2) is a member of the NR5A class of NRs that regulate the expression of genes central to embryonic development, cell cycle progression, reproduction, and lipid homeostasis (1) in response to activating PLs (2). This family includes steroidogenic factor-1 (SF-1; NR5A1) and Drosophila melanogaster fushi tarazu factor 1 (Ftz-F1; NR5A3).…”
mentioning
confidence: 99%
“…Phospholipids play critical signaling roles as second messengers in a number of cellular signaling cascades via their derivatives and cleavage products 29 . It has been reported that phospholipids have anti-inflammatory action on acute exudation of inflammatory modes induced by LPS 30 , but the direct immune of PLs has barely reported.…”
Section: Discussionmentioning
confidence: 99%